PERAN PEMERINTAH DALAM DIPLOMASI PERDAGANGAN PRODUK KULIT INDONESIA BERDASARKAN ANALISIS GLOBAL VALUE CHAIN STUDI KASUS DI DAERAH ISTIMEWA YOGYAKARTA - , Silvi Dian Permatasa, Dra. Siti Daulah Khoiriati, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Many countries believe the global value chain very wide influence on global trade. Free trade has made the commodity markets widely open, but on otherside some countries by showing non-tariff barriers in international trade. Diplomacy with the global value chain framework is needed considering the problems that appeared attacking upper and lower trade. The success of trade diplomacy is indicated when the final product chains become export products instead of import products of a country. This research aims to explain whether government policy can affect the competitiveness of leather products in the international market The international leather industry covers a lot of stuff, countries, and actors with a variety of different rules. The leather products are also marketed from simple to complex ways. Based on that situation, is needs more than one type of governance so the Government could play a role in diplomacy skin products. Government as the market is believed to transform into modular or even a relation supplier in order to succeed the trade diplomacy. Global value chain that prioritizes the industry hilirisasi is not an instant diplomacy whose results can be seen in one or two years. However, there is a parameter which indicates that trade diplomacy has been running those are: 1) The Indonesian leather products have been oriented to final chain export or finished product which is a primary goal of global value chain, 2) The purpose of Indonesia export products has been diversified in many countries. It shows that the tariff and non-tariff barriers have been reduced through diplomacy, 3) Indonesian skin products has been diversified into many types of products which shows the strong interest in the market to the products and it shows that Indonesia leather survive from the invasion of foreign products.